Step * 1 1 2 1 1 1 of Lemma cos-sin-equation


1. : ℝ ⟶ ℝ
2. : ℝ ⟶ ℝ
3. ∀x,y:ℝ.  ((x y)  (f(x) f(y)))
4. ∀x,y:ℝ.  ((x y)  (g(x) g(y)))
5. ∀x,y:ℝ.  (f(x y) ((f(x) f(y)) (g(x) g(y))))
6. : ℝ
7. f(a) ≠ f(r0)
8. ¬(∃b:ℝg(-(b)) ≠ g(b))
9. ∀b:ℝ(g(-(b)) g(b))
10. ∀x,y:ℝ.  (f(x y) f(y x))
11. ∀y:ℝ(f(-(y)) f(y))
12. ∀x,y:ℝ.  (f(x -(y)) f(x y))
13. f(a) f(r0)
⊢ ¬¬((∃c:ℝ
       ((r0 ≤ (c c^2)) ∧ (∀x:ℝ(f(x) c)) ∧ ((∀x:ℝ(g(x) rsqrt(c c^2))) ∨ (∀x:ℝ(g(x) -(rsqrt(c c^2)))))))
∨ (∃a:ℝ(a ≠ r0 ∧ (∀x:ℝ(f(x) rcos(a x))) ∧ (∀x:ℝ(g(x) rsin(a x))))))
BY
((RWO "-1" THENA Auto) THEN FLemma `rneq_irreflexivity` [7] THEN Auto) }


Latex:


Latex:

1.  f  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
2.  g  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
3.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (f(x)  =  f(y)))
4.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (g(x)  =  g(y)))
5.  \mforall{}x,y:\mBbbR{}.    (f(x  -  y)  =  ((f(x)  *  f(y))  +  (g(x)  *  g(y))))
6.  a  :  \mBbbR{}
7.  f(a)  \mneq{}  f(r0)
8.  \mneg{}(\mexists{}b:\mBbbR{}.  g(-(b))  \mneq{}  g(b))
9.  \mforall{}b:\mBbbR{}.  (g(-(b))  =  g(b))
10.  \mforall{}x,y:\mBbbR{}.    (f(x  -  y)  =  f(y  -  x))
11.  \mforall{}y:\mBbbR{}.  (f(-(y))  =  f(y))
12.  \mforall{}x,y:\mBbbR{}.    (f(x  -  -(y))  =  f(x  -  y))
13.  f(a)  =  f(r0)
\mvdash{}  \mneg{}\mneg{}((\mexists{}c:\mBbbR{}
              ((r0  \mleq{}  (c  -  c\^{}2))
              \mwedge{}  (\mforall{}x:\mBbbR{}.  (f(x)  =  c))
              \mwedge{}  ((\mforall{}x:\mBbbR{}.  (g(x)  =  rsqrt(c  -  c\^{}2)))  \mvee{}  (\mforall{}x:\mBbbR{}.  (g(x)  =  -(rsqrt(c  -  c\^{}2)))))))
\mvee{}  (\mexists{}a:\mBbbR{}.  (a  \mneq{}  r0  \mwedge{}  (\mforall{}x:\mBbbR{}.  (f(x)  =  rcos(a  *  x)))  \mwedge{}  (\mforall{}x:\mBbbR{}.  (g(x)  =  rsin(a  *  x))))))


By


Latex:
((RWO  "-1"  7  THENA  Auto)  THEN  FLemma  `rneq\_irreflexivity`  [7]  THEN  Auto)




Home Index